Measurements of the radar cross section of a nano-drone at K-band - Balleri, Alessio (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Nano-drones, are insect-like sized drones with a threat capability of intrusion to provide intelligence and potentially violate secure establishments and public privacy rights. They are an existing technology which is becoming increasingly more available, portable, affordable and easy to operate. As such, they represent a plausible defence and security threat. In this paper, a setup is presented that is used to measure the 3-dimensional Radar Cross Section (RCS) of a nano-drone for three elevation planes with a 5-degree resolution step in azimuth and elevation. The results presented in this paper are unique because there has been very little work, if any, in the existing literature attempting to measure the RCS of such small drones. They are also key to inform further work investigating the development of nano-drone detection radar systems as well as nano-drone detection and classification signal processing solutions.
Keywords: Radar Cross Section (RCS); nano-drones; pico-drones; drone signatures; drone classification; drone recognition; drone detection